Hubungan Minat Belajar Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Di SMP - Fransiskus Obianus Mari; Yuliana Tamu Ina Nuhamara; Elsy Sanides Hana Taunu (Universitas Hamzanwadi, 2026)
Describing the relationship between learning interest and students’ mathematical problem-solving abilities in junior high school. The study employed a descriptive qualitative approach supported by simple quantitative data. The subjects were classified based on learning interest categories, namely low, moderate, and high. Data collection was carried out through tests, questionnaires, interviews, and documentation, while the analysis applied the Miles and Huberman model consisting of data reduction, data presentation, verification, and conclusion drawing. The findings revealed that students’ mathematical problem-solving abilities were still low. Students with high learning interest tended to be more capable of understanding problems, determining solution steps, applying strategies, rechecking answers, and drawing conclusions in accordance with Polya’s stages. In contrast, students with low learning interest still experienced difficulties in determining formulas, arranging solution steps, and reviewing their answers. The findings indicate that learning interest has an important role in supporting students’ problem-solving abilities.